Effects Of User Experience (Ux) On Fitness Band Usage And Healthy Lifestyle - Noor, Nurdayana Mohamad (2021)
The aim of this thesis is to deploy and develop user experience (UX) theory from human computer interaction (HCI) in predicting the usage of fitness bands as an emerging wearable technology and its impact on the users’ healthy lifestyle. The study identifies which UX factors drive the fitness bands usage and how it can contribute to health communication, specifically in addressing Malaysian alarming health issues. The theory of UX mainly focuses on the technology neglecting human factors which have great potential to drive the usage of new technology. The significance of the study is that it informs the theoretical understanding of fitness band usage by introducing the application of self-efficacy along with need for self-tracking as human factors. The study adopts the snowballing and purposive sampling techniques to recruit 280 qualified respondents. Data collected through a structured questionnaire were analysed using the Partial Least Square Structural Equation Modelling (PLS-SEM). The study performs the data analysis through measurement model analysis (content validity –pilot testing, convergent validity – Cronbach alpha, composite reliability, and average variance extracted, and discriminant validity – Fornell-Larcker and HTMT criteria) and structural model analysis (coefficient of determination, effect size, and predictive relevance). The findings reveal that usability and utility have significant positive effects on fitness bands usage. The inclusion of the human factors to advance the model of UX theory was found insignificant in predicting the usage.